International student support and engagement in higher education exploring innovative practices in campus, academic and professional support services - Mohamed, Mutiara; Boyd, Janet 1967- (New York Routledge, 2023)
"International Student Support and Engagement in Higher Education examines innovative practices in campus, academic, and professional support services which serve the various and unique needs of international students seeking undergraduate and graduate degrees. Divided into three sections pertaining to campus, academic and professional support services, the authors present case studies and original research that examine strategies for how institutions of higher education can operate to promote international student success beyond the classroom. The international range of contributors showcase research from across Canada, China, Indonesia, Malaysia, Russia, Senegal, Thailand and the US. Foregrounding support services with innovative and successful methods for collaborating with one another, the book crucially addresses how the myriad support services available on campuses can work together to support international students and foster a sense of belonging and connection, rather than maintaining a focus on acculturation. It examines the origins of these partnerships, asking whether the services are designed to support the international student community specifically, or to serve the student population more generally. Identifying new emerging trends and with a view to establishing a broad and global context for best practices in international student support, this book will appeal to faculty, researchers, scholars, and scholar-practitioners with interests in higher education, student support services and international and comparative education"--
Trends, challenges, and opportunities in supporting and engaging international students / Janet Boyd and Mutiara Mohamad -- How Chinese international student engagement in the United States differs from domestic student engagement / Rong Wang -- 'Belonging' at a liberal arts college : creating emotional and physical spaces of home / Andrew Meade, Charlotte Ong, and Sahara Pradhan -- Making students feel at home through a student ambassadorship program : the Universiti Kebangsaan Malaysia experience / Yazrina Yahya and Doria Binti Abdullah -- Academic (dis)engagement of international doctoral students at Russian universities / Evgeniy Terentev, Taylor Woodman, Anna Grigoryeva, and Ekaterina Minaeva -- How soccer can serve as a conceptual model for structuring an international student support office / Peter Briggs and Ravichandran Ammigan -- Exploring the relationship between academic performance and the international student experience : implications for university support offices and academic unit / Ravichandran Ammigan and Matthew L. Drexler -- Supporting (Chinese) international students' academic and social needs in socioculturally-attuned ways / Tang T. Heng -- The promise and limits of engaging international students through living-learning communities in U.S. research universities / Gerardo L. Blanco, Bin Zhao and Boying Ji -- Multilingual international students' perceptions of support services from an identity perspective / Vander Tavares -- Navigating student visas in the United States : policy, practice, and implications / Adam Grimm and Bristol Day -- Chinese international students at two Canadian universities : learning from their emotional labor to re-align support services / Guanglong Pang and Jean Michel Montsion -- International students' career preparation / Defta Oktafiga, Allison Brcka Lorenz, and Yihan Zhu -- Bridging the gap between higher education and rapidly changing labor markets / Nancy Chervin, Hélène Cyr, Nora Nunn, and Taania Tzelnic -- Supporting the support services : a call for universities to include international student support services in their strategic plans / Janet Boyd and Mutiara Mohamad.
Includes bibliographical references and index.
Keywords: College environment; College student development programs; Student adjustment; Student affairs services; Students, Foreign -- Services for